2017
DOI: 10.1371/journal.pone.0178409
|View full text |Cite
|
Sign up to set email alerts
|

Safety and EEG data quality of concurrent high-density EEG and high-speed fMRI at 3 Tesla

Abstract: PurposeConcurrent EEG and fMRI is increasingly used to characterize the spatial-temporal dynamics of brain activity. However, most studies to date have been limited to conventional echo-planar imaging (EPI). There is considerable interest in integrating recently developed high-speed fMRI methods with high-density EEG to increase temporal resolution and sensitivity for task-based and resting state fMRI, and for detecting interictal spikes in epilepsy. In the present study using concurrent high-density EEG and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
(40 reference statements)
0
24
2
Order By: Relevance
“…Quality comparison of EEG data has been investigated between simultaneous and separate recordings by visual inspection (Laufs et al, 2003; Foged et al, 2017) and simulation studies (Ihalainen et al, 2015). More quantitative spectral approaches for comparing measurements have been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality comparison of EEG data has been investigated between simultaneous and separate recordings by visual inspection (Laufs et al, 2003; Foged et al, 2017) and simulation studies (Ihalainen et al, 2015). More quantitative spectral approaches for comparing measurements have been described.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that for weaker effects this might not be the case. fMRI TR duration is considered of limited influence (Foged et al, 2017). The regional effects found in this study are somewhat different from these described in the literature (Luo and Glover, 2012; Ihalainen et al, 2015; Klein et al, 2015), underlining that for every individual set-up a quality test is advisable.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the increase in temperature (∼0.8°C) in the Tp8 electrode, which also has a relatively long lead, the removal of the ECG lead alone is unlikely to ensure that high SAR sequences can be run safely with EEG system present. These findings are in general agreement with recent work that also considered safety implication of MB (Foged et al, ). It is also important to note that minimal heating effects were observed at the MRI scanner bore location suggesting that the MR scanning was not increasing the ambient temperature of the bore.…”
Section: Discussionmentioning
confidence: 99%
“…This was necessary because it is not customary to acquire MB-EPI data simultaneously with EEG and at the time of the experiment, this was the first study to do so according to our knowledge. However, at the time that this report was being peer-reviewed, we learned that others had performed simultaneous multiband fMRI and EEG, albeit with different equipment (Lewis et al, 2016 ; Foged et al, 2017 ). In fact Foged et al showed, using temperature measurements, that it is safe to combine high density EEG with fast fMRI techniques such as multiband EPI (Foged et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, at the time that this report was being peer-reviewed, we learned that others had performed simultaneous multiband fMRI and EEG, albeit with different equipment (Lewis et al, 2016 ; Foged et al, 2017 ). In fact Foged et al showed, using temperature measurements, that it is safe to combine high density EEG with fast fMRI techniques such as multiband EPI (Foged et al, 2017 ). Subsequent to our in-house testing, the procedure was approved by Auburn University's Institutional Review Board (IRB) as well as the MR safety committee.…”
Section: Methodsmentioning
confidence: 99%